Demographic Correlates of Anxiety and Depression Symptoms in Chronic Sinonasal Diseases. (August 2014) - Katotomichelakis, Michael; Simopoulos, Efthimios; Tzikos, Anthimos; Balatsouras, Dimitrios; Tripsianis, Gregory; Danielides, Gerasimos; Xenitidis, Kiriakos; Livaditis, Miltos; Danielides, Vassilios
Objectives: To explore mental health of patients with olfactory loss due to chronic sinonasal diseases and investigate the effects of age-, gender-, and socio-economic variables on anxiety and depression symptoms. Methodology: One hundred and eight patients (62 males; mean age: 39.78 ± 16.11 years), suffering from olfactory impairment due to chronic rhinosinusitis and allergic rhinitis and 30 healthy subjects (16 males; mean age, 37.03 ± 13.09 years) were studied. Olfactory function was evaluated using "Sniffin' Sticks" test. All patients completed four validated questionnaires specific for assessing anxiety and depression (Zung Anxiety Scale, State-Trait Anxiety Inventory-STAI, Zung Depression Scale, and Beck Depression Inventory-BDI). Results: We found significantly more severe anxiety and depression symptoms in anosmic (all p < 0.001) and hyposmic patients compared to healthy controls. No significant differences were observed between normosmic patients and controls. Scores in all psychological measures were significantly higher in elderly and female patients as well as in low, compared to high, socio-economic status patients. No significant differences were found between low and medium socio-economic level. Conclusions: Olfactory loss in chronic sinonasal diseases was found to be associated with anxiety and depression symptoms. Moreover, anxiety was correlated with depression. With regard to patients' demographics, female gender and low socioeconomic status proved to be independently correlated with anxiety and depression levels.